2020
DOI: 10.5539/gjhs.v12n3p110
|View full text |Cite
|
Sign up to set email alerts
|

The Utilization of Long-Acting Reversible Contraception and Associated Factors Among Women in Indonesia

Abstract: Long-acting reversible contraceptives (LARCs), consist of IUD and implats, were effective and efficient methods in preventing the pregnancy. However, the used of these methods in Indonesia was still low. This study sought to explore LARC utilization trends and the factors influencing LARC used among reproductive women in Indonesia. This research analyzed data from the Indonesia Demographic and Health Survey 2017. Respondents in this study were women who currently used modern contraceptive methods. A total of 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
7
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 28 publications
3
7
0
1
Order By: Relevance
“…This advantage demonstrates the need for more effective and long-term contraceptive options even in the less formally educated women. These findings are similar to observations in Malawi, Zimbabwe [ 11 ], Indonesia [ 13 ], and most other low and middle countries [ 27 ]. While education level impacted the overall use of contraceptives in Ghana, Zambia, and Madagascar, it did not impact the choice of the method used [ 28 ].…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…This advantage demonstrates the need for more effective and long-term contraceptive options even in the less formally educated women. These findings are similar to observations in Malawi, Zimbabwe [ 11 ], Indonesia [ 13 ], and most other low and middle countries [ 27 ]. While education level impacted the overall use of contraceptives in Ghana, Zambia, and Madagascar, it did not impact the choice of the method used [ 28 ].…”
Section: Discussionsupporting
confidence: 90%
“…This may be because most women marry at an early age (median age: 19.2 years in Tanzania) [ 18 ], typically conceiving immediately after marriage and thus ruling out the need for LARCs in their teenage years. A similar relationship was observed in other sub-Saharan nations [ 11 ], Nigeria [ 9 ], the USA [ 10 , 24 ], and Indonesia [ 13 ]. Interestingly, women in Zambia aged below 25 years did not use LARCs [ 25 ].…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…A study by Gayatri (2020) explains about analyzing women throughout Indonesia using the 2017 IDHS data, which showed that women who were visited by field workers had a higher chance of using long-term reversible contraceptive methods than women who were not visited. However, the proportion of women visited by the field workers was less than 4%.…”
Section: Discussionmentioning
confidence: 99%